Cataloguing and computer networking in libraries - Malik, Cyrus (Delhi Edukeen, 2024)
Cataloging or Cataloguing or Library Cataloging is the process of creating and maintaining bibliographic and authority records in the library catalog, the database of books, serials, sound recordings, moving images, cartographic materials, computer files, e-resources etc. that are owned by a library. The catalog may be in tangible form, such as a card catalog or in electronic form, such as online public access catalog (OPAC). Library and information networks have the potential to improve library services in several ways. It brings down the cost of information products and services in the network environment in shared mode. It enables libraries to offer need - based services to the end users eliminating the limitation of size, distance and language barriers among them. With evolution in library networks, the emphasis has moved from the networks as physical entities to the resources available through the networks. These network-accessible resources include databases of library holdings, journal articles, electronic text, images, video and audio files, scientific and technical data, etc. This comprehensive book will prove an ideal reference work for students and professionals in library science.
Keywords: Library Science; Library, Archives, Information Centers; Library- Computer Networking